Efficiency of implementation of state environmental projects to achieve sustainable development of subjects of the Russian Federation - Artem D. Kozlov; Zhanna A. Mingaleva (Наука Красноярья)
The environmental well-being of individual countries, regions, and entities are topical issues for both individuals and businesses, as well as for government and administrative bodies. Projects and programs to improve the environmental situation and combat climate change cover all subjects of society and are adopted at different levels of the hierarchy. The growth in the number of such projects and the scale of their coverage of various aspects of society’s life makes the question of the effectiveness of their implementation increasingly relevant.